Effects of different light sources on microleakage of composite resins with different monomer structures - Fikret Yilmaz; Nihan Gonulol; Eda Guler; Engin Ersoz; Fatma Aytac (Elsevier, 2014)
Background/purpose: The aim of this study was to investigate the effects of different light curing units (LCUs) on the microleakage of different composite resins. Materials and methods: Forty-five freshly extracted human third molars were selected for this study. Standardized class V cavities were prepared on the buccal and lingual surfaces of each tooth. The teeth were randomly divided into three composite resin groups, comprising two dimethacrylate-based hybrid composites and a silorane-based composite. Each composite resin group was randomly divided into three subgroups for curing with three different LCUs (n = 5). Of the three different LCUs used, one was quartz-tungsten-halogen and two were light-emitting diodes (LEDs) with different power outputs. The teeth were immersed in a 2% methylene blue dye solution and examined under a stereomicroscope. Results were statistically analyzed using Kruskal-Wallis and Dunn tests. Results: When all composite resin groups were compared, the lowest marginal leakage scores were obtained with the Filtek Silorane composite group, and they statistically significantly differed from those of the other groups (P < 0.05). Among all groups, the lowest marginal leakage value was obtained for the LED 1055 subgroup of the Filtek Silorane composite group, and the highest marginal leakage value was obtained for the quartz-tungsten-halogen subgroup of the Aelite Aesthetic Enamel composite group. Conclusion: It was concluded that it is not possible to entirely prevent microleakage, but it can be minimized with silorane-based composite resins and high-density-output LED LCUs.